Effect of Timing on Visual Outcomes in Fovea-Involving Retinal Detachments Verified by SD-OCT. (22nd February 2020) - Angermann, Reinhard; Bechrakis, Nikolaos E.; Rauchegger, Teresa; Casazza, Marina; Nowosielski, Yvonne; Zehetner, Claus
Abstract : Purpose . To investigate the impact of surgical delay after the objectivation of the foveal status by spectral-domain optical coherence tomography (SD-OCT) on visual outcomes in patients with rhegmatogenous retinal detachment (RRD) with foveal involvement. Methods . A retrospective dataset analysis of 508 eyes of 504 consecutive patients with primary RRD was performed. The primary outcome measure was the best-corrected visual acuity as a function of time between the assessment of the foveal status with SD-OCT upon initial examination at the department and RRD repair. Results . In total, 188 eyes (37.0%) had a complete foveal detachment and 31 (6.1%) eyes had a bisected fovea by the retinal detachment. A hundred eyes with total foveal detachment received surgery within 24 h and 65 eyes between 24 h and 72 h. Visual outcomes for eyes with detached fovea were significantly better when treated within 24 h (0.47 ± 0.39) compared with those treated between 24 h and 72 h (0.84 ± 0.66; p = 0.01 ) after objectivation of the foveal status with SD-OCT. Pars plana vitrectomy was performed in 174 (92.6%) eyes and scleral buckling surgery in 14 (7.4%) eyes with complete foveal involvement of RRD. Conclusions . Our findings suggest improved visual outcomes for patients receiving surgery within 24 h after a definitive diagnosis of fovea-involving RRD compared to surgical interventions that were further delayed.